2013
DOI: 10.2485/jhtb.22.409
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Diameter of Honeycomb Tunnel Structure induces Bone Regeneration and Metabolism by Promoting Angiogenesis for an Implant Circumference Bone Defect

Abstract: To develop an effective method of bone augmentation for dental implants, particularly for patients with a scarce amount of bone, we introduced a new honeycomb-like -tricalcium phosphate (H--TCP) as a scaffold, whose unique geometrical properties induce bone formation along with vasculature. A total of six beagles from 6 to 7 years old were used for this study. Autologous bone marrow-derived mesenchymal cells (BMC) cultured with H--TCP were implanted around the dental implants, and healing was compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, biomaterials other than TCP need the presence of growth factors and stem cells for bone formation, whereas honeycomb TCP do not need their factors for bone formation [22][23][24][25][26][27][28]. In addition, there are many studies focusing on geometrical structures, and it has been reported that it is necessary to provide an appropriate microenvironment such as pore structure for bone tissue formation [4,5,8,9,[12][13][14][15][16]18,20,21]. However, although there are some studies that change the pore size of the same material, there is no study that changes the direction of the holes as in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, biomaterials other than TCP need the presence of growth factors and stem cells for bone formation, whereas honeycomb TCP do not need their factors for bone formation [22][23][24][25][26][27][28]. In addition, there are many studies focusing on geometrical structures, and it has been reported that it is necessary to provide an appropriate microenvironment such as pore structure for bone tissue formation [4,5,8,9,[12][13][14][15][16]18,20,21]. However, although there are some studies that change the pore size of the same material, there is no study that changes the direction of the holes as in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been reported that the geometrical structure of artificial biomaterials exerts a great influence on the process of hard tissue formation [12,13], and porosity is particularly important for cell proliferation and differentiation and vascular invasion [14]. Generally, when the pores of artificial biomaterials are too large, the stiffness of the porous body becomes weak, and when the pores are too small, the stiffness increases but cells and blood vessels have difficulty entering the pores [12][13][14][15][16]. At present, artificial biomaterials with high porosity have been developed and have already been clinically applied.…”
Section: Introductionmentioning
confidence: 99%